2016
DOI: 10.5194/isprs-archives-xli-b8-417-2016
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Discrimination of the Thick Oil Patches on the Sea Surface

Abstract: Commission VIII, WG VIII/5 KEY WORDS: Oil slick thickness, offshore slick, SWIR, VNIR, optical multispectral data, hyperspectral characterization, reflectance spectra ABSTRACT:Detection of natural or accidental oil slick at sea surface is important both for exploration purposes and for environment protection. Radar imagery, either satellite or airborne is the prime tool to detect those slicks. Radar is widely used by the national agencies to monitor their maritime areas for accidental pollutions or boat discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Based on these observations, Clark et al 12 developed oil thickness maps from a few AVIRIS flight lines collected on May 17, 2010, including uncertainties in these estimates. More recently, Dubucq et al 46 also demonstrated that SWIR wavelengths are useful for detecting thick oil slicks.…”
Section: Remote Detection and Characterization Of Surface Oilmentioning
confidence: 99%
“…Based on these observations, Clark et al 12 developed oil thickness maps from a few AVIRIS flight lines collected on May 17, 2010, including uncertainties in these estimates. More recently, Dubucq et al 46 also demonstrated that SWIR wavelengths are useful for detecting thick oil slicks.…”
Section: Remote Detection and Characterization Of Surface Oilmentioning
confidence: 99%